Siege! : Princes Gate, London, April 30-May 5 : Sunday Times, Insight, On the Great Embassy Rescue - Hamlyn Paperbacks (London Hamlyn Paperbacks, 1980)
In 1980 the world watched as gunmen held 26 people hostage at the Iranian embassy in London. After a six-day stand-off the SAS launched a dramatic attack on the hostage-takers. Countless words have been written about the London Embassy Siege. But who were the gunmen? What was it like inside? What were the moves in the psychological chess game? How did the SAS pull off its dramatic rescue? The renowned Insight team of the Sunday Times has pieced this extraordinary story together. This is what really happened.
Includes Illustrations and Epilogue
Keywords: Terrorism -- England--London